The figure “teacher-writer” by J. Williams: novel “Stoner” - Kalynych, Kateryna (Pitannâ lìteraturoznavstva, 2020)
The realization of the paradigm “teacher-writer” in the interpretation of American professor and writer John Williams has been researched. The comparison of the author’s biography with the image of the protagonist of the novel – Stoner – revealed that the latter is the prototype of the writer. Along with the evolution development of the main character William Stoner, we have followed the improvement of his teaching methods which was reflected on the pages of the novel. The reader’s attention is logically focused on the main issues, such as the war theme and the mission of the university. It was shown how political events (World Wars I and II) consistently influenced the functioning of the educational institution having direct impact on the behavior of the studenthood. The author puts forward his own concept of the real nature of an academic institution thus defining three university models. The first model – “the Stoner model” – renders a closed institution which cluster the chosen ones in order to implement ideal concepts of scientific activity; the second – “the Finch model” – demonstrates an open institution which realizes its educational and spiritual activities for an appropriate reward; the third model, knows as “Masters model”, sees a university as a shelter for incompetent people and elderly unfulfilled personalities. The conclusions lies in the notion of “perfect education” witch should be specific for any given epoch. For instance, according to J. William’s novel, new realia demand of university to renew its concepts and priorities, the lack of which, in its turn, reasons the logic of the conflict between the past and the present, and this is what the character of William Stoner systematically faces, apparently reflecting the experience of the author himself.